The Value of Traditional Medicine Should not be Underestimated-Traditional Chinese Medicine in Treatment of Autoimmune Diseases - Yurii O Novikov; Anait P Akopyan; Zhiheng GUO (Wolters Kluwer Health/LWW, 2024)
Abstract. Autoimmune diseases of the nervous system (ADNS) are characterized by the formation of a pronounced neurologic deficit and often lead to disability. The attention of doctors and researchers is increasingly attracted by complementary medicine as adjuvant or preventive therapy for various diseases, including autoimmune diseases. Traditional Chinese medicine (TCM) is a combination of treatment methods that include acupuncture, herbal medicine, dietetics, physical exercises, and other methods that are often used in conjunction with recognized approaches of official medical science. The article describes the application of TCM techniques in autoimmune diseases of the nervous system, and demonstrates clinical experience in the use of acupuncture, herbal medicine, diets and physical exercises. Traditional and complementary medicine is an important and often underestimated healthcare resource, especially in the prevention and treatment of autoimmune diseases of the nervous system.